The use of ArcGIS to determine the relationship between crop yield performance and soil properties. A case study in Semujuk Jasin / Norkhairunisa Abdul Shukor - Abdul Shukor, Norkhairunisa (Faculty of Plantation and Agrotechnology, 2018)
Soil nutrient is essential for crop growth. Spatial variability of nutrient will be occurred in numerous scales, between region, a field, particularly in soil properties. In agriculture practice, Graphic Information System (GIS) is widely used especially in farm management, crop monitoring and land assessment and planning. A study was carried out to observe the yield performance in an agricultural plot at Semujuk Jasin, Melaka. Using management zone delianisation, the area divded into fifteen smaller 6.8 meter x 6.8 meter plot. Soil sample from each plot was tested in the laboratory to obtain the soil moisture, organic matter, pH level, Phosphorus and Manganese content. Using ArcGIS software, the result is interpolated using Kringging method, mapped and then compared with crop value from each plot to determine the factor affecting crop yield performance. Each plot planted with 160 corn plant. Full yield capacity for each plot is RM160. Five plot with soil moisture less than 20% show poor yield performance that is below RM80. The lowest yield generated by plot A3 with crop yield value of RM6.8. This plot also has the lowest soil moisture content that is 6.452%. Plot A1 produce only RM65.2 for crop yield although have 21.505% of soil moisture content while plot C1 only produce RM47.4 for crop yield value although have a higher soil moisture content that is 23.265%. When referred to the soil organic matter content for both plots, plot A1 has only 1.455% of organic matter content while plot C1 has lower soil organic matter content that is 0.823%. Plot B2 with low pH value (4.51) show poor performance that is RM52.6 regarding satisfactory reading on other reading. Phosphorus and Manganese show the insignificant impact on the yield performance. This indicates that both nutrient level is satisfactory through the study area. The suggestion made to improve yield performance for next cycle by increasing the irrigation period for a plot with low moisture content. Sandy loam soil has a good aeration and drainage, but it cannot hold water on longer period of time. By increasing the irrigation time, the soil moisture can be increase. For plot with low pH value, applying 10kg of Ground Magnesium Lime is suggested to be added at each plot. For a plot with organic matter content lower than average value 5% (A1, C1), 20kg of chicken dung is suggested to be added at each plot. From the analysis made based on the experiment result, the primary limiting factor affecting the crop performance is soil moisture content. Soil pH value and Organic Matter also play an essential role in determining crop performance. By using ArcGIS, the process of determining all the factor are faster, more comfortable and more accurate.